Weighted least absolute value power system state estimation using rectangular coordinates and equivalent measurement functions - Rakpenthai C. (2014)
This paper presents a new efficient computation technique for robust power system state estimation based on weighted least absolute value (WLAV) criterion. The proposed method employs rectangular form of state variables and equivalent measurements technique in order to obtain the linear measurement functions with linear constraints of state variables. The state estimation problem is then formulated as an optimization problem with a set of equality and inequality constraints. A solution method based on interior point algorithm is also proposed. Tests with several IEEE standard systems have been performed to investigate the performance of the proposed algorithm. Results indicate that the proposed state estimator gives promising performance compared with weighted least square (WLS) based estimation algorithms using state variables in polar forms. © 2011 Institute of Electrical Engineers of Japan.